2017
DOI: 10.21608/asejaiqjsae.2017.4198
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Tree Species Diversity in Dry Forest of East Nusa Tenggara, Indonesia

Abstract: We examined structure, diversity and importance value index (IVI) of tree species in dry forests of Binafun, Bonmuti, Letkole and Oelbanu, Mutis Timau Conservation Forest Management Unit, East Nusa Tenggara province, Indonesia. To obtain data on the composition and diversity of vegetation carried out through the analysis of tree species using sampling plots in a rectangular shape, with a size of 100 m x 100 m at 100 m intervals. Results of tree species list showed that there were 94 species belong to 45 famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…It is shown from its IVI compared with the other trees species (Figure 10). This result is in line with the previous study which showed that E. urophylla dominated the vegetation of Nature Reserve of Mount Mutis, East Nusa Tenggara province (Almulqu et al, 2017). Lewotobi, Mutis, and Timau (BKLH, 2013).…”
Section: Vegetation At 500-700 M Aslsupporting
confidence: 93%
“…It is shown from its IVI compared with the other trees species (Figure 10). This result is in line with the previous study which showed that E. urophylla dominated the vegetation of Nature Reserve of Mount Mutis, East Nusa Tenggara province (Almulqu et al, 2017). Lewotobi, Mutis, and Timau (BKLH, 2013).…”
Section: Vegetation At 500-700 M Aslsupporting
confidence: 93%
“…In 1997, the local government conducted reforestation using E. urophylla as the primary species for rehabilitation. In addition to having a rapid growth, E. urophylla is a native species from this location (Almulqu et al, 2019). Therefore, the implementation of reforestation is also expected to support conservation for indigenous species from East Nusa Tenggara.…”
Section: Methodsmentioning
confidence: 99%
“…This area has geographic coordinates of S9°50′0″ to S9°50′15″ and E124°15′30″ to E124°16′0″ ( ), Figure 1 while the topography is dominated by hilly terrain with a slope level ranging from 15 to 45%. Moreover, the altitude reaches 800 m asl (Almulqu et al, 2019), while the area is classified as humid, with an average air humidity of 85.5% and a daily average temperature of 29 °C. The annual rainfall -1 -1…”
Section: Methodsmentioning
confidence: 99%